2006
DOI: 10.1177/000348940611500304
|View full text |Cite
|
Sign up to set email alerts
|

Virtual versus Conventional Laryngeal Endoscopy

Abstract: We have evaluated the capacity of virtual laryngoscopy and conventional laryngoscopy conducted with a rigid or flexible instrument to visualize laryngeal structures in 64 patients with normal endoluminal anatomy. Virtual laryngoscopy allowed total visualization of laryngeal structures, including those that could not be reached by a flexible instrument. There was good correlation between virtual laryngoscopy and "real" images, indicating satisfactory diagnostic accuracy (p < .05). Although virtual laryngoscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This finding highlights the importance of CT-VE in the endoscopic representation of the anatomical structures and the utility of this modality as a complement to other techniques. 9 This correlation has already been estimated by Businco 12 who described satisfactory diagnostic accuracy. Furthermore, Byrne et al.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This finding highlights the importance of CT-VE in the endoscopic representation of the anatomical structures and the utility of this modality as a complement to other techniques. 9 This correlation has already been estimated by Businco 12 who described satisfactory diagnostic accuracy. Furthermore, Byrne et al.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, Magnano 10 described other factors such as swallowing, phonation and breathing that decrease the image quality and limit the assessment of these structures. In disagreement to these reports, some studies 12 , 13 have reported high accuracy of VE in lesions localised in the vocal cords. However, Walshe 14 described that it is important to have an air mucosa interface and mucosal distortion in order to be able to identify lesions.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation